Assessment of nociceptive system in vegetative and minimally conscious state by using laser evoked potentials. (15th October 2015) - De Salvo, S.; Naro, A.; Bonanno, L.; Russo, M.; Muscarà, N.; Bramanti, P.; Marino, S.
Abstract: Primary objective : The aim of this study is to assess if laser evoked potentials (LEPs) examination should be considered as an objective evidence of potential or residual pain perception capacity in vegetative (VS) and minimally conscious state (MCS) patients and if it could be a feasible methodology in order to differentiate these two clinical entities. Research design : This is a cross-sectional observational study focusing on the role of LEP examination, which is an easy and objective neurophysiological approach of the nociceptive system. Methods and procedures : Thirteen VS and 10 MCS patients were enrolled. All subjects were evaluated clinically by using validated behavioural scales and underwent to upper and lower limbs LEP recording. Main outcomes and results : Intra-group LEPs analysis in VS patients highlighted significant differences for N2P2 latency ( p  = 0.036) and amplitude ( p  = 0.018). Inter-group LEPs analysis showed significant differences in post-anoxic condition for N2P2 latency ( p  = 0.034), amplitude ( p  = 0.034) and a trend in N2P2 latency in brain trauma ( p  = 0.07). Interestingly, correlation analysis showed a significant relationship between N2P2 amplitude and Coma Recovery Scale-Revised scoring in the post-traumatic VS ( r  = 0.823, p  = 0.044). Conclusions : The findings lead to detection of potential markers of conscious pain perception in patients with DOC, with important impact on therapeutic and rehabilitative management, and provide new information that may allow a better differential diagnosis.